2017
DOI: 10.1002/berj.3265
|View full text |Cite
|
Sign up to set email alerts
|

School composition, school culture and socioeconomic inequalities in young people's health: Multi‐level analysis of the Health Behaviour in School‐aged Children (HBSC) survey in Wales

Abstract: Health inequalities emerge during childhood and youth, before widening in adulthood. Theorising, testing and interrupting the mechanisms through which inequalities are perpetuated and sustained is vital. Schools are viewed as settings through which inequality in young people's health may be addressed, but few studies examine the social processes via which institutional structures reproduce or mitigate health inequalities. Informed by Markham and Aveyard's theory of human functioning and school organisation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 39 publications
(61 reference statements)
6
39
0
Order By: Relevance
“…However, this may lead to an oversight of the more deprived students who are attending more affluent schools who report poorer relationships with school staff (Moore et al, 2017). Thus, work should be undertaken to investigate any role that models for the distribution of well-being support roles within schools may play in mitigating or perpetuating inequalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may lead to an oversight of the more deprived students who are attending more affluent schools who report poorer relationships with school staff (Moore et al, 2017). Thus, work should be undertaken to investigate any role that models for the distribution of well-being support roles within schools may play in mitigating or perpetuating inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ relationships with their teachers and with other students in the school environment are consistently predictive of a broad range of health and well-being outcomes (Bonell et al, 2013; Moore et al, 2017; Suldo et al, 2009). Interventions such as INCLUSIVE (Bonell et al, 2014b), a school environment intervention to tackle bullying, attempt to work with the pre-existing functioning of school systems and better orient these school environments towards supporting health.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, social inequalities in adolescents' wellbeing are often measured by examining disparities in adolescents' socioeconomic status (SES) while social capital is largely overlooked. Socioeconomic status (SES) has been found to impact health and wellbeing directly [2,[8][9][10][11] and indirectly through psychosocial factors such as the poor's inability to establish bonds and networks for their benefits [6,7,11]. These psychosocial factors, however, can function as protective mechanisms to offset some effects of SES inequalities on wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…We sought to repeat and extend the analyses done by Moore et al . (). We found that pupils from less affluent families tend to report a lower sense of belonging and lower commitment to academic values but not worse relationships with teachers or participative school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al's analysis provided evidence suggesting that pupil-staff relationships are a key mechanism underlying the worse health of disadvantaged pupils in more affluent schools: poor relationships with staff were predicted by a pupil's position within the school's socio-economic status (SES) hierarchy and associated with worse health outcomes (Moore et al, 2017). Students from the poorest families reported better relationships with teachers where they attended less affluent schools.…”
Section: Introductionmentioning
confidence: 99%